A method for the systematic assessment of lubricant performance during superplastic sheet forming: Verfahren zur systematischen Bewertung der Schmierstoffleistung bei der superplastischen Blechumformung. Issue 10 (19th October 2017) - Farrell, M.; Drabek, M.; Qarni, M.J.
Abstract: Frictional forces at the die‐sheet interface during superplastic forming play an important role in controlling material flow. As such, lubricious coatings are routinely used to facilitate a low friction flow of sheet metal into the die cavity. They may also act as parting agents and/or oxidation barriers. The selection of coatings for the superplastic forming of Ti‐6Al‐4 V is limited by the requirement of thermomechanical stability at the high forming temperature, therefore, solid film coatings such as boron nitride are a common choice. However, little work has been published on coating performance during superplastic forming, particularly under true process conditions. This paper presents a method for the systematic assessment of superplastic forming coating performance by using a multi‐pocket die, which allows many coating types and combinations to be tested simultaneously during a single forming cycle. Sixteen coating combinations were evaluated in total and the resultant sheet thickness distributions compared, serving as an indicator of friction.